Membangun Empati Remaja terhadap Korban Bullying melalui Komik Digital - Anisah Firdaus; Arif Sutrisno; Nuril Kusuma Wardani (Wimba : Jurnal Komunikasi Visual, 2025)
Bullying is a repeated act of physical or psychological harm that causes victims to feel oppressed, powerless, and even traumatized. This issue remains prevalent among adolescents, as indicated by KPAI data. This study aims to provide education while raising awareness and empathy among adolescents toward bullying victims through digital comics published on Webtoon, a popular platform in Indonesia. The research employs the ADDIE method (Analysis, Design, Development, Implementation, and Evaluation). The result of this study is a digital comic titled Rough, a drama and angst-themed series consisting of five episodes. The story portrays the struggles of the main character as a bullying victim and conveys educational messages through its narrative. Expert validation in media and content resulted in scores of 93.66% and 94%, respectively. A trial involving 30 tenth-grade students at SMA Negeri 8 Malang achieved an average score of 89.64%, proving that Rough is an effective educational medium for fostering adolescent empathy toward bullying victims.